Perturbation Theory for Weak Measurements in Quantum Mechanics, Systems with Finite-Dimensional State Space - Ballesteros, Miguel; Crawford, Nick; Fraas, Martin; Fröhlich, Jürg; Schubnel, Baptiste (Annales Henri Poincaré, 2019)
The quantum theory of indirect measurements in physical systems is studied. The example of an indirect measurement of an observable represented by a self-adjoint operator N with finite spectrum is analyzed in detail. The Hamiltonian generating the time evolution of the system in the absence of direct measurements is assumed to be given by the sum of a term commuting with N and a small perturbation not commuting with N . The system is subject to repeated direct (projective) measurements using a single instrument whose action on the state of the system commutes with N . If the Hamiltonian commutes with the observable N (i.e., if the perturbation vanishes), the state of the system approaches an eigenstate of N , as the number of direct measurements tends to ∞ . If the perturbation term in the Hamiltonian does not commute with N , the system exhibits “jumps” between different eigenstates of N . We determine the rate of these jumps to leading order in the strength of the perturbation and show that if time is rescaled appropriately a maximum likelihood estimate of N approaches a Markovian jump process on the spectrum of N , as the strength of the perturbation tends to 0.